2012
DOI: 10.1016/j.freeradbiomed.2011.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a redox-sensitive switch within the JAK2 catalytic domain

Abstract: Four cysteine residues (Cys866, Cys917, Cysl094, and Cys1105) have direct roles in cooperatively regulating Janus kinase 2 (JAK2) catalytic activity. Additional site-directed mutagenesis experiments now provide evidence that two of these residues (Cys866 and Cys917) act together as a redox-sensitive switch, allowing JAK2's catalytic activity to be directly regulated by the redox state of the cell. We created several variants of the truncated JAK2 (GST/(NΔ661)rJAK2), which incorporated cysteine-to-serine or cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…Expression levels of Jak2 and p-Stat3 decreased when neurons were exposed to OGD/R, indicating an attenuated Jak2/Stat3 signal. A site-directed mutagenesis experiment revealed that cysteine residues, Cys866 and Cys917, act as a redox-sensitive switch controlling the catalytic activity of Jak2 (29). However, there are inconsistencies regarding changes in Jak2 activity under oxidized conditions in previous reports (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression levels of Jak2 and p-Stat3 decreased when neurons were exposed to OGD/R, indicating an attenuated Jak2/Stat3 signal. A site-directed mutagenesis experiment revealed that cysteine residues, Cys866 and Cys917, act as a redox-sensitive switch controlling the catalytic activity of Jak2 (29). However, there are inconsistencies regarding changes in Jak2 activity under oxidized conditions in previous reports (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are inconsistencies regarding changes in Jak2 activity under oxidized conditions in previous reports (30,31). Research has suggested that Jak2 activity in response to oxidative stress may also be dependent on the cell line used, due to difference in structural elements of Jak2 (29). In neurons, Jak2 activity is attenuated by oxidative stress induced by cadmium, with a deficiency of Jak2/Stat3 signaling (32).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with PTPs, which are always inhibited by ROS, the oxidation of PTKs can lead to both enhancement and inhibition of kinase activity (26,27).…”
Section: Sulfenic Acid Formation and Reactivitymentioning
confidence: 99%
“…Keap1 is responsive to general oxidative stress stimuli as well as intracellular ROS production from NADPH oxidase [13]. Recently, Smith et al have provided evidence suggesting that a cysteine-based redox-sensitive switch may exist in the non-receptor tyrosine kinase JAK2, and may regulate JAK2 catalytic activity [14]. JAK2 is the upstream kinase responsible for phosphorylation and activation of the transcription factor STAT following stimulation by multiple cytokines; activation of STAT proteins regulates cell proliferation, survival and myeloid development.…”
Section: Editorialmentioning
confidence: 99%
“…JAK2 is the upstream kinase responsible for phosphorylation and activation of the transcription factor STAT following stimulation by multiple cytokines; activation of STAT proteins regulates cell proliferation, survival and myeloid development. It has been demonstrated that two cysteine residues (866 and 917) may act together as a redox-sensitive switch, allowing catalytic activity of JAK2 to be directly regulated by the redox state of the cell; consistently, the activity of a JAK2 mutant in which these two cysteines are replaced by alanine is redox insensitive [14]. Interestingly, another study has shown that STAT3 can also be regulated by redox changes via a different mechanism, involving the thiol peroxidase peroxiredoxin-2 [15].…”
Section: Editorialmentioning
confidence: 99%